The legend of Zelda : Ocarina of Time / 1. - Himekawa, Akira (VIZ Media, 2008)
Link embarks on a quest to deliver the spiritual stone of the forest to Zelda, princess of the land of Hyrule, while encountering many dangers and fighting evil.